Fresh spirulina biomass for human nutrition – safety, microbiology, storage, sensorics - Claudia Marcela Vasquez Guevara; Simona Lucakova; Tereza Branysova; Vojtech Ilko; Adam Tobolka; Ales Rajchl; Irena Branyikova (Journal of Applied Phycology, 2025)

Growth dynamics and climate sensitivities in alpine cushion plants: insights from Silene acaulis in the Swiss Alps - Samresh Rai; Nikola Breme; Veronika Jandova; Vojtech Lanta; Jan Altman; Adam Taylor Ruka; Christian Rixen; Jiri Dolezal (Alpine Botany, 2025)
Understanding alpine plants’ growth dynamics and responses to warming is essential for predicting climate change impacts on mountain ecosystems. Here, we examine growth determinants in the alpine cushion plant Silene acaulis in the Swiss Alps, exploring ontogeny, elevation, and climate influences. We collected 40 Silene individuals and 159 individuals from 38 co-occurring alpine species across 2200–3130 m elevations in the Swiss Alps, analyzing age and growth histories through annual growth rings. While comparing growth rates, we found that Silene was relatively slow-growing. However, Silene exhibited a dual growth strategy, initially rapid and then slowing after ~ 20 years, challenging perceptions of its longevity. Similar ontogenetic trends were observed in other alpine species, albeit with variations based on species and elevation. The consistent unimodal growth-elevation pattern in Silene and other alpine plants, peaking at ~ 2400 m, underscores shared environmental constraints on alpine plant growth. Additionally, cross-dating growth ring series and correlating with daily climate data enabled the precise assessment of warming impacts on growth. Silene ’s growth is influenced by year-to-year climate variability, with warming-induced moisture stress and overheating during spring and summer adversely affecting its growth. Despite being low-statured, Silene is not completely decoupled from atmospheric influences. The heat-trapping function of Silene , effective in mature and well-formed cushions, makes it susceptible to adverse effects as temperatures rise. This sensitivity raises concerns about the potential dieback of Silene cushions, as witnessed during recent heatwaves, and emphasizes the broader ecological implications for alpine ecosystems, given Silene ’s role as a crucial nurse plant.

Advanced chemically modified electrodes and platforms in food analysis and monitoring - Ivana Tomac; Vojtech Adam; Jan Labuda (Food Chemistry, 2024)

Antioxidant-related enzymes and peptides as biomarkers of metallic nanoparticles (eco)toxicity in the aquatic environment - Tomas Do; Silvia Vaculciakova; Katarzyna Kluska; Manuel David Peris-Díaz; Jan Priborsky; Roman Guran; Artur Krężel; Vojtech Adam; Ondrej Zitka (Chemosphere, 2024)

The role of cellular senescence in neurodegenerative diseases - Yating Wang; Kamil Kuca; Li You; Eugenie Nepovimova; Zbynek Heger; Marian Valko; Vojtech Adam; Qinghua Wu; Klaudia Jomova (Archives of Toxicology, 2024)
Increasing evidence has revealed that cellular senescence drives NDs, including Alzheimer’s disease (AD) and Parkinson’s disease. Different senescent cell populations secrete senescence-associated secretory phenotypes (SASP), including matrix metalloproteinase-3, interleukin (IL)-1α, IL-6, and IL-8, which can harm adjacent microglia. Moreover, these cells possess high expression levels of senescence hallmarks (p16 and p21) and elevated senescence-associated β-galactosidase activity in in vitro and in vivo ND models. These senescence phenotypes contribute to the deposition of β-amyloid and tau-protein tangles. Selective clearance of senescent cells and SASP regulation by inhibiting p38/mitogen-activated protein kinase and nuclear factor kappa B signaling attenuate β-amyloid load and prevent tau-protein tangle deposition, thereby improving cognitive performance in AD mouse models. In addition, telomere shortening, a cellular senescence biomarker, is associated with increased ND risks. Telomere dysfunction causes cellular senescence, stimulating IL-6, tumor necrosis factor-α, and IL-1β secretions. The forced expression of telomerase activators prevents cellular senescence, yielding considerable neuroprotective effects. This review elucidates the mechanism of cellular senescence in ND pathogenesis, suggesting strategies to eliminate or restore senescent cells to a normal phenotype for treating such diseases.

Microalgae/cyanobacteria: the potential green future of vitamin B 12 production - Michaela Durdakova; Martina Kolackova; Anna Janova; Olga Krystofova; Vojtech Adam; Dalibor Huska (Critical Reviews in Food Science and Nutrition, 2024)

Optimizing Communication in Ataxia: A Multifaceted Approach to Alternative and Augmentative Communication (AAC) - Adam P. Vogel; Caroline Spencer; Katie Burke; Daniella de Bruyn; Peter Gibilisco; Scott Blackman; Jennifer M. Vojtech; Thayabaran Kathiresan (The Cerebellum, 2024)
The progression of multisystem neurodegenerative diseases such as ataxia significantly impacts speech and communication, necessitating adaptive clinical care strategies. With the deterioration of speech, Alternative and Augmentative Communication (AAC) can play an ever increasing role in daily life for individuals with ataxia. This review describes the spectrum of AAC resources available, ranging from unaided gestures and sign language to high-tech solutions like speech-generating devices (SGDs) and eye-tracking technology. Despite the availability of various AAC tools, their efficacy is often compromised by the physical limitations inherent in ataxia, including upper limb ataxia and visual disturbances. Traditional speech-to-text algorithms and eye gaze technology face challenges in accuracy and efficiency due to the atypical speech and movement patterns associated with the disease. In addressing these challenges, maintaining existing speech abilities through rehabilitation is prioritized, complemented by advances in digital therapeutics to provide home-based treatments. Simultaneously, projects incorporating AI driven solutions aim to enhance the intelligibility of dysarthric speech through improved speech-to-text accuracy. This review discusses the complex needs assessment for AAC in ataxia, emphasizing the dynamic nature of the disease and the importance of regular reassessment to tailor communication strategies to the changing abilities of the individual. It also highlights the necessity of multidisciplinary involvement for effective AAC assessment and intervention. The future of AAC looks promising with developments in brain-computer interfaces and the potential of voice banking, although their application in ataxia requires further exploration.

Nanoarchitectonics of graphene based sensors for food safety monitoring - Vedran Milosavljevic; Katerina Mitrevska; Milica Gagic; Vojtech Adam (Critical Reviews in Food Science and Nutrition, 2023)

Physiological and transcriptome profiling of Chlorella sorokiniana: A study on azo dye wastewater decolorization - Vladimira Tarbajova; Martina Kolackova; Pavel Chaloupsky; Marketa Dobesova; Petr Capal; Zdenek Pilat; Ota Samek; Pavel Zemanek; Pavel Svec; Dagmar Skopalova Sterbova; Marketa Vaculovicova; Lukas Richtera; et al. (Journal of Hazardous Materials, 2023)

c-Jun N-terminal kinase signaling in cellular senescence - Ying Deng; Vojtech Adam; Eugenie Nepovimova; Zbynek Heger; Marian Valko; Qinghua Wu; Wei Wei; Kamil Kuca (Archives of Toxicology, 2023)

Microplastics and nanoplastics toxicity assays: A revision towards to environmental-relevance in water environment - Ondrej Pencik; Michaela Durdakova; Katarina Molnarova; Attila Kucsera; Daniel Klofac; Martina Kolackova; Vojtech Adam; Dalibor Huska (Journal of Hazardous Materials, 2023)

Not so dangerous? PET microplastics toxicity on freshwater microalgae and cyanobacteria - Ondrej Pencik; Katarina Molnarova; Michaela Durdakova; Martina Kolackova; Daniel Klofac; Attilla Kucsera; Petr Capal; Pavel Svec; Zuzana Bytesnikova; Lukas Richtera; Martin Brtnický; Vojtech Adam; et al. (Environmental Pollution, 2023)

A “2 + 2” strategy for tumor immune microenvironment remodeling based on complementary immune checkpoint blockade - Yue Zhou; Siyu Wang; Xiaoyang Liang; Zbynek Heger; Qiang Lu; Wen Li; Vojtech Adam; Nan Li (Chemical Engineering Journal, 2023)

Role of secondary metabolites in distressed microalgae - Martina Kolackova; Anna Janova; Marketa Dobesova; Monika Zvalova; Pavel Chaloupsky; Olga Krystofova; Vojtech Adam; Dalibor Huska (Environmental Research, 2023)

Transcriptomic hallmarks of in vitro TiO2 nanotubes toxicity in Chlamydomonas reinhardtii - Marketa Dobesova; Martina Kolackova; Ondrej Pencik; Petr Capal; Pavel Chaloupsky; Pavel Svec; Andrea Ridoskova; Martin Motola; Veronika Cicmancova; Hanna Sopha; Jan.M. Macak; Lukas Richtera; et al. (Aquatic Toxicology, 2023)

Graphene oxide as a tool for antibiotic-resistant gene removal: a review - Zuzana Bytesnikova; Lukas Richtera; Kristyna Smerkova; Vojtech Adam (Environmental Science and Pollution Research, 2019)

Zinc and zinc-containing biomolecules in childhood brain tumors - Jan Hrabeta; Tomas Eckschlager; Marie Stiborova; Zbynek Heger; Sona Krizkova; Vojtech Adam (Journal of Molecular Medicine, 2016)

The role of sulphur in cadmium(II) ions detoxification demonstrated in in vitro model: Dionaea muscipula Ell. - Petr Babula; Pavel Ryant; Vojtech Adam; Josef Zehnalek; Ladislav Havel; Rene Kizek (Environmental Chemistry Letters, 2009)

Uncommon heavy metals, metalloids and their plant toxicity: a review - Petr Babula; Vojtech Adam; Radka Opatrilova; Josef Zehnalek; Ladislav Havel; Rene Kizek (Environmental Chemistry Letters, 2008)

Determination of content of metallothionein and low molecular mass stress peptides in transgenic tobacco plants - Vaclav Diopan; Violetta Shestivska; Vojtech Adam; Tomas Macek; Martina Mackova; Ladislav Havel; Rene Kizek (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)